Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.21203/rs.2.23279/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intra-carotid arterial transfusion of circulatory-derived autologous endothelial progenitor cells in rodent after ischemic stroke — evaluating the impact of therapeutic time points on prognostic outcomes

Abstract: Background: This study tested the optimal time point for left intra-carotid arterial (LICA) administration of circulatory-derived autologous endothelial progenitor cells (EPCs) for improving the outcome in rat after acute ischemic stroke (IS). Methods and Results: Adult-male SD rats (n=70) were equally categorized into group 1 (sham-operated control), group 2 (IS), group 3 (IS+EPCs/1.2x106 cells/by LICA administration 3h after IS), group 4 (IS+EPCs/LICA administration post-day-3 IS), group 5 (IS+EPCs/LICA admi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
2
3
0
1
Order By: Relevance
“…In this way, our finding corroborated with the finding of our previous studies [31,32,38,39]. Interestingly, our other previous studies have revealed that early administration of stem cells was more advantageous than the late administration of stem cells on protecting the organ from ischemia and hypoxia induced damage [40,41]. Of importance was that the result of the present study identified that early administration was better than late administration of iPS-MSCs on improving the prognostic outcome.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this way, our finding corroborated with the finding of our previous studies [31,32,38,39]. Interestingly, our other previous studies have revealed that early administration of stem cells was more advantageous than the late administration of stem cells on protecting the organ from ischemia and hypoxia induced damage [40,41]. Of importance was that the result of the present study identified that early administration was better than late administration of iPS-MSCs on improving the prognostic outcome.…”
Section: Discussionsupporting
confidence: 92%
“…Of importance was that the result of the present study identified that early administration was better than late administration of iPS-MSCs on improving the prognostic outcome. Accordingly, the result of this study was consistent with those from our previous studies [40,41]. Of particularly important finding was that combined iPS-MSCs and ciprofloxacin was superior to either one alone for protecting the kidney organ and improving the prognostic outcome, highlighting that this strategic management may serve as a therapeutic protection for those severe sepsis patients complicated with major organ failure and are refractory to conventional treatment.…”
Section: Discussionsupporting
confidence: 89%
“…We proposed the therapeutic regimen of the multiple dosages of HUCDMSCs (ie like the regimen of antibiotics to be utilized for treatment the bacterial‐induced sepsis in our daily clinical practice) could be the key to success for remarkable preservation of the brain architecture and neurological function. Interestingly, our previous 36 and recent 37 studies have shown that early and multiple dosages of stem cell administration was the crucial role on reducing the post‐heart transplant acute rejection 36 and preservation of the neurological function after acute ischaemic stroke 37 in rodent. In this way, the results of the present study, in addition to being comparable with the findings of our previous 36 and recent 37 studies, highlight that this regimen could be seriously considered in our future stem cell therapy for the patients.…”
Section: Discussionmentioning
confidence: 98%
“…We proposed the therapeutic regimen of the multiple dosages of HUCDMSCs (i.e., like the regimen of antibiotics to be utilized for treatment the bacterial-induced sepsis in our daily clinical practice) could be the key to success for remarkable preservation the brain architecture and neurological function. Interestingly, our previous [36] and recent [37] studies have shown that early and multiple dosages of stem cell administration was the crucial role on reducing the post-heart transplant acute rejection [37] and preservation of the neurological function after acute ischemic stroke [38] in rodent. In this way, the results of the present study, in addition to being comparable with the ndings of our previous [36] and recent [37] studies, highlight that this regimen could be seriously considered in our future stem cell therapy for the patients.…”
Section: Discussionmentioning
confidence: 99%